ANALYSIS OF EXPERIMENTAL TEST RESULTS OF CURRENT AND NEW COMPOSITION COLONS - Sarimsakov Olimjon Sharipjanovich; Ergashev Sharibboy Tulanovich; Shokirov Khasanboy Tuychiboy o‘g‘li (The American Journal of Engineering and Technology, 2024)
In the process of separating cotton fiber from seed in a sawed fiber separator, the formation of raw material depends on several factors. The most important of them are the speed of rotation of the raw material, fiber, density, the amount of seeds separated from the fiber, etc. In addition, it is necessary to take into account the force of friction created by the walls of the working chamber due to the pressure created in the raw material. A high coefficient of friction of the colossal working surface has a negative effect on work efficiency, in particular, frictional forces cause the seed separated from the fiber to remain on the colossal working surface. These factors have an effect on the performance of the fiber separator and the quality of the extracted fiber. It is known that in the process of ginning, 25% of the fiber and seeds separated from the fiber remain in the raw material pile, causing mechanical damage. The main goal of the research is to prevent fiber and seed damage in the process of separating cotton fiber from the seed by installing a colosnik structure with the new recommended composition, to increase the efficiency of the seed exit from the working chamber, and at the same time to study ways to reduce energy consumption during the ginning process. This research paper presents an analysis of the results obtained after installing one of the working parts of the gin machine on the DL-10 gin machine of the existing and recommended composition of colosniks. The main purpose of introducing the new construction is to increase the efficiency of the DL-10 gin machine of the society, to develop it by filling it with new technologies, and to obtain quality fiber and seed.